Long-Term and Seasonal Changes in Sources of Urban Atmospheric Particulates in the Western Pacific - Kazuichi Hayakawa; Ning Tang; Akira Toriba (Applied Sciences, 2022)
To reduce atmospheric pollutants, the sources need to be identified. To this end, combustion-derived particulates (Pc) in atmospheric suspended particulate matter (TSP) in ten Western Pacific cities from 1997 to 2018 were analyzed using the NP method, which we have recently developed. The method separates Pc into particulates originating from high-temperature (Ph) and low-temperature (Pl) combustion sources. Using this method, ten cities in the Asia-Pacific region were separated into three classes. Class 1: commercial cities whose major contributor to Pc was from vehicles, and which showed lower [Pc] values with larger [Ph]/[Pc] ratios. Sapporo, Kanazawa, Tokyo, Sagamihara (Japan), Shanghai (China), and Busan (Korea) were contained in this class. Class 2: cities whose main source of Pc was from coal heating, and which showed much higher winter [Pc] with larger [Pl]/[Pc] ratios. Beijing, Shenyang (China), and Vladivostok (Russia) were contained in this class. Class 3: steel manufacturing city which showed lower [Pc] with larger [Pl]/[Pc] ratio. The low [Pc] appeared to be due to elimination of Pl from coke oven plants. Only Kitakyushu was contained in this class. This study has elucidated the contribution of sources to urban atmospheric TSP in the Western Pacific that was previously unknown. Overall [Pc] was decreasing in this region, mainly due to the decreasing contribution of vehicles to Pc, but not due to a decrease in coal combustion.